2019
DOI: 10.1093/femsec/fiz113
|View full text |Cite
|
Sign up to set email alerts
|

Multiple factors drive the abundance and diversity of the diazotrophic community in typical farmland soils of China

Abstract: Biological nitrogen fixation plays an important role in nitrogen cycling by transferring atmospheric N2 to plant-available N in the soil. However, the diazotrophic activity and distribution in different types of soils remain to be further explored. In this study, 152 upland soils were sampled to examine the diazotrophic abundance, nitrogenase activity, diversity and community composition by quantitative polymerase chain reaction, acetylene reduction assay and the MiSeq sequencing of nifH genes, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 52 publications
3
56
4
Order By: Relevance
“…Furthermore, our data showed that geographic distance exerted greater impacts on microbial community structure than environmental dissimilarity did ( Figure S6, Table S5). By contrasting to the overwhelming contribution of soil depth over paddy soil groups to microbial community studied here, the great impact of soil types on microbiomes was reported previously at larger scales [3,6,18,24] . Han et al reported that soil types possessed signi cant divergence in diazotrophic community in the topsoil of farmland, which was signi cantly affected by spatial distance, climate and soil properties [3] .…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Furthermore, our data showed that geographic distance exerted greater impacts on microbial community structure than environmental dissimilarity did ( Figure S6, Table S5). By contrasting to the overwhelming contribution of soil depth over paddy soil groups to microbial community studied here, the great impact of soil types on microbiomes was reported previously at larger scales [3,6,18,24] . Han et al reported that soil types possessed signi cant divergence in diazotrophic community in the topsoil of farmland, which was signi cantly affected by spatial distance, climate and soil properties [3] .…”
Section: Discussioncontrasting
confidence: 99%
“…By contrasting to the overwhelming contribution of soil depth over paddy soil groups to microbial community studied here, the great impact of soil types on microbiomes was reported previously at larger scales [3,6,18,24] . Han et al reported that soil types possessed signi cant divergence in diazotrophic community in the topsoil of farmland, which was signi cantly affected by spatial distance, climate and soil properties [3] . Bai et al (2017) showed that soil type exerted more signi cant impacts on bacterial and fungal diversity than soil pro le did with distant geographic distances (e.g.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations